Collaborative Public Health Surveillance Strategies to Address Local Health Needs - Padron, Norma (International Journal of Population Data Science, 2018)
Introduction This presentation will review the current strategies being used by health care delivery systems across the US to incorporate via linkage, publicly available data assets. The discussion will focus on lessons learned with a specific emphasis of collaborations between health systems to address the opioid crisis. Objectives and Approach To review ongoing strategies to incorporate local, publicly available data assets to clinical data assets that health systems have for purposes of collaborations with public health surveillance. The emphasis of the discussion presented will be in the data strategies that local health departments and health care delivery systems have used to address the opioid crisis in the US. This presentation will propose strategies to be explored and bring forth concerns about data fairness, accountability and transparency when collaborations for public health surveillance are in place. Results The presentation will discuss the experiences learned in specific regions in the United States. The main results will center around assessing the effectiveness of current strategies to share and analyze data across health care delivery systems and local agencies and government partners. The lessons learned of what works and what hasn't will be discussed in light of the ongoing epidemic of opioid use and drug overdose deaths in the United States. Finally the presentation will present strategies that could be explored for collaborative public health surveillance that address issues and concers of fairness, accountability and transparency. Conclusion/Implications The implications of this report and presentation is that ongoing data linkage and sharing strategies have been -for the most part- insufficient to enable delivery systems and local public health departments and government address rising epidemiological concerns. The proposed strategies complement what is being done and advance data-driven public health